Center-Pivot-Irrigated Forage Sorghum Silage Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S.; Martin, Kent L. (My University, 2011)
This publication estimates the costs and returns associated with center-pivot-irrigated forage sorghum put up as silage in western Kansas.
MF998_2011_12
Keywords: MF998; Economics; Crops; MF